First principles study of structural stability, electronic structure and mechanical properties of ReN and TcN. (March 2015) - Rajeswarapalanichamy, R.; Kavitha, M.; Sudha Priyanga, G.; Iyakutti, K.
Abstract: The crystal structure, structural stability, electronic and mechanical properties of ReN and TcN are investigated using first principles calculations. We have considered five different crystal structures: NaCl, zinc blende (ZB), NiAs, tungsten carbide (WC) and wurtzite (WZ). Among these ZB phase is found to be the lowest energy phase for ReN and TcN at normal pressure. Pressure induced structural phase transitions from ZB to WZ phase at 214 GPa in ReN and ZB to NiAs phase at 171 GPa in TcN are predicted. The electronic structure reveals that both ReN and TcN are metallic in nature. The computed elastic constants indicate that both the nitrides are mechanically stable. As ReN in NiAs phase has high bulk and shear moduli and low Poisson's ratio, it is found to be a potential ultra incompressible super hard material. Graphical abstract: Highlights: Structural, electronic and mechanical properties of ReN and TcN are studied. A pressure induced structural phase transition is predicted. Electronic structure reveals that both ReN and TcN exhibit metallic behavior. High bulk modulus indicates that ReN and TcN are superhard materials. ReN and TcN are mechanically stable in ZB phase at ambient condition.